Leptin gene (TTTC)n microsatellite polymorphism as well as leptin receptor R223Q and PPARγ2 P12A substitutions are not associated with hypertensive disorders in pregnancy - Wiedemann, Annette Lucia; Vocke, Franziska; Fitzgerald, Justine S.; Markert, Udo R.; Jeschke, Udo; Lohse, Peter; Toth, Bettina (American journal of reproductive immunology, 2010)
Citation Wiedemann A, Vocke F, Fitzgerald JS, Markert UR, Jeschke U, Lohse P, Toth B. Leptin gene (TTTC)n microsatellite polymorphism as well as Leptin receptor R223Q and PPARγ2 P12A substitutions are not associated with hypertensive disorders in pregnancy. Am J Reprod Immunol 2010; 63: 310-317 Problem Pregnancy-induced hypertension (PIH) affects up to 15% of all pregnancies. Disturbed placentation is one factor associated with PIH. Leptin and peroxisome proliferator activator receptors (PPAR) seem to play an important role in placentation, fetal development, and blood pressure regulation. Therefore, we investigated polymorphisms in the genes encoding leptin, the leptin receptor, and PPARγ2 in patients with PIH. Method of study In this retrospective case-control study, 103 patients with PIH [gestational hypertension (GH) n = 39; preeclampsia n = 27; eclampsia n = 5; HELLP n = 32] and 100 controls were analyzed for the LEP tetranucleotide repeat (TTTC)n and the leptin receptor (LEPR) R223Q and PPARγ2 P12A substitutions. Statistical analysis was performed using the chi-square, Mann-Whitney U-, and Kruskal-Wallis tests (P < 0.05 significant). Results The frequency of the three possible genotypes did not differ significantly between patients and controls [LEP (TTTC)n: P = 0.43; LEPR R223Q: P = 0.94; PPARγ2 P12A: P = 0.94]. However, postpartal diastolic blood pressure of PIH patients was significantly higher in homozygous carriers of the LEPR Q223-encoding allele as compared with patients carrying the wild-type allele (P < 0.01). Conclusion Hypertensive disorders in pregnancy were not associated with the LEP, LEPR, and PPARγ2 polymorphisms studied. The role of other variations in the LEP and PPAR genes in the pathophysiology of PIH and in exacerbations are the objective of ongoing research.
Das n in (TTTC)n und das γ in PPARγ2 im Titel sind tiefgestellt
First published: 10 March 2010
Gesehen am 29.01.2024